THE EFFECT OF EMPLOYEE PERSONALITY ON SALES PERFORMANCE BASED ON EXTROVERT AND INTROVERT TYPE OF PERSONALITY (CASE STUDY : EMPLOYEE AT ALLIANZ LIFE INSURANCE IN MANADO) - Abidin, Reynaldi Abryan Zainal (Jurnal Berkala Ilmiah Efisiensi, 2016)
Personality is an important factor that affected performance, quality and achievement in the workplace. It is best to discover and understand the personality of employees to ensure that the company needs and employees are fulfilled and also to empower in order to successfully achieve the objectives. This research aims to identify employees’ sales performance based on their personality that is distinguished into extrovert and introvert. The data is collected from the interviews of nine respondents in an insurance company. The result shows: (1) employees or agents who have introvert personality are having good performance and successful on meeting the daily target; (2) employees or agents with extrovert personality are also performing good and successful in meeting the daily target. The difference is that the more extroverted employees responded with more opinions or answers during the interview. In conclusion, the performance of all respondents is excellent regardless of their basic personality.